A Systematic Review of Exit Exams in Higher Education: The Upsides and Downsides - Samson Worku Teshome (Management of Education: Jurnal Manajemen Pendidikan Islam, 2025)
Exit exams in higher education have both upsides and downsides. This review examines their impact using the PRISMA methodology. It analyzes 22 empirical studies published between 1994 and 2024. The search covered databases like Google Scholar, ERIC, PubMed, Scopus, and Web of Science. A thematic narrative synthesis was used to evaluate the findings. Exit exams improve accountability and standardize assessments. They align curricula with learning goals. This ensures consistent educational quality across institutions. Students gain job-ready skills, enhancing employability. Exams also promote critical thinking and inclusivity. However, downsides exist. High-stakes exams increase student stress and anxiety. They may lead to "teaching to the test," narrowing curricula. Creativity and deeper learning can suffer. Equity concerns arise due to cultural and socioeconomic disparities. Underrepresented groups often face disadvantages. The review highlights a need for balance. While exams raise standards, their risks must be managed. Support systems can reduce student stress. Diverse assessment methods should complement exams. Equitable access to resources is crucial. Policymakers and educators must collaborate for fair practices. Ongoing research is needed. Future studies should explore long-term impacts on students. Cross-cultural comparisons can identify best practices. Alternative assessment models may offer solutions. Addressing equity gaps remains a priority. In conclusion, exit exams have clear upsides but significant downsides. A balanced approach is essential. This ensures that exams enhance education without harming students. Continuous evaluation and adaptation are key to maximizing upsides while minimizing harm.